The Prognostic Role of MET Protein Expression Among Surgically Resected Non-small Cell Lung Cancer Patients: A Meta-Analysis - Ma, Guangzhi; Deng, Yunfu; Chen, Wenjie; Liu, Zhenkun; Ai, Cheng; Li, Xuebing; Zhou, Qinghua (Frontiers in Oncology, 2019)
Objectives: MET protein expression has been reported to be in relevance with the survival of NSCLC patients in various studies, yet the results were inconsistent. The purpose of our study set out to determine the prognostic role of both c-MET and p-MET expression among NSCLC that underwent surgical resection. Methods: Data were obtained from retrospective cohort studies by searching on PubMed, Cochrane Library, EMBASE and Web of Science and a meta-analysis was performed to assess the prognostic role of MET expression among NSCLC. Results: Totally 18 literatures including 5572 surgically resected NSCLC cases staged I-IV were included for data synthesis. The positive rate of c-MET and p-MET was 1753/4315 and 135/1257. The pooled hazard ratios (HRs) regarding c-MET and p-MET expression for overall survival (OS) was 1.623 (95% CI: 1.176-2.240, p=0.003) and 1.710 (95% CI: 0.823-3.533, p=0.15), respectively. Subgroup analysis results on Asian (HR=2.115, p<0.001), adenocarcinoma (HR=2.220, p<0.001) and rabbit polyclonal antibodies (HR=2.107, p<0.001) etc. were also indicative. Conclusion: C-MET over-expression among NSCLC patients that underwent surgical resection is a prognostic factor that indicated adverse survival on OS. Whereas p-met didn’t appear to have an impact on the prognosis of NSCLC. The studies are need and the topic could be re-valued by then.